Revitalisasi Kesenian Rakyat Borobudur dalam Perspektif Estetika Religius Walter Benjamin - Chotimah, Chusnul (Societas Dei: Jurnal Agama dan Masyarakat, 2024)
This article aims to capture the dynamics of Borobudur folk art, which experiences ups and downs. Some people believe that the decline of folk art initially impacted the emergence of television, one of the modernist instruments. By using that logic, folk art ideally is running to its extinction. However, in recent years, the Borobudur community has successfully revitalised the folk art that has been dead for decades, such as ketoprak. On the other hand, the Borobudur community has unique religious characteristics; They are plural in terms of religion but hold the same Javanese values. To understand the dynamics, this article uses Walter Benjamin's theory of religious aesthetics as an analytical tool. Specifically, this article will answer two research questions: How does religiosity influence folk art revitalization, and what is the social function of folk art for the Borobudur Community? This qualitative research was conducted in Borobudur District in 2022 using an ethnographic approach.